ANALISIS PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN SUB SEKTOR ROKOK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2023 - Soares, Abil Osario; Kamil, Musthafa (LP2M Universitas Bina Bangsa, 2025)
This research is motivated by the existence of the cigarette industry in Indonesia which has given rise to a dilemma in society. This study aims to analyze the comparative financial performance of cigarette sub-sector companies listed on the Indonesia Stock Exchange for the 2021-2023 period. To find out for sure how the company is performing, a proper analysis is needed through financial reports. The data collection method in compiling this thesis is the documentation method and literature study with the analysis method in the form of non-statistical analysis, namely the data analysis method without using statistical analysis. This study uses data samples from the financial reports of cigarette sub-sector companies listed on the Indonesia Stock Exchange for the 2021-2023 period. There are 4 cigarette issuers whose shares are listed on the IDX, namely Gudang Garam Tbk (GGRM), Handjaya Mandala Sampoerna Tbk (HMSP), Tobacco Indonesia Tbk (ITIC), and Wismilak Inti Makmur (WIIM). The results of the study show that 1) The WIIM Liquidity Ratio Value is the best compared to the industry average value, 2) The HMSP Solvency Ratio Value is the best compared to the industry average value, 3) The HMSP & WIIM Profitability Ratio Value is the best compared to the industry average value.